Effectiveness of Class C fly ash as an expansive soil stabilizer - Nalbantoglu, Z (Elsevier Sci Ltd, 2004)
Fly ash produced in the combustion of subbituminous coals exhibits self-cementing characteristics and can be used in a wide range of stabilization applications. Fly ash treatment can effectively reduce the swell potential of highly plastic clays and prevent the swell beneath the smaller foundation pressures. The geology and climatic condition in Cyprus produce a wide distribution of expansive soils. These soils present problems in construction and possess a variety of undesirable characteristics such as low strength, high plasticity, difficult compaction and high swell potential. Laboratory test results on these soils indicate that fly ash is effective in ameliorating the texture and plasticity of the fly ash treated soils by reducing the amount of clay size particles, plasticity index and the swell potential. Cation exchange is one of the important reactions responsible for the improvement in the soil characteristics. In the study, cation exchange capacity (CEC) values have been used to indicate the changes in the mineralogy of the fly ash treated soils and explain the reduction in the plasticity and water absorption potential. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: expansive soils; fly ash; stabilization